ANALYSIS OF PARABOLIC EQUATION (RAMGEO) PROPAGATION MODEL IN NORTH NATUNA SEA - Agustinus, Agustinus; Manik, Henry Munandar; Sukoco, Nawanto Budi; Muharrom, Eka Yudha; Supriyanto, Taufiq (Transpublika Publisher, 2024)
The waters of the North Natuna Sea are one of Indonesia's conflict-prone maritime areas, frequently traversed by foreign vessels due to its direct border with several neighboring countries, necessitating effective maritime security assurance. To ensure this security, meticulous sea control and surveillance, particularly through the utilization of monitoring tools such as SONAR to detect foreign objects traversing or entering the North Natuna Sea waters, are required. This research aims to analyze the characteristics of underwater acoustic wave propagation patterns, particularly in the formation of silent areas or Shadow Zones, using the Parabolic Equation method (RAMGeo). Parabolic Equation propagation model (RAMGeo) simulations are conducted utilizing the AcTUP v2.2L Toolbox. Temperature and salinity data against depth obtained from Marine Copernicus for one year are utilized in this study, spanning from January 1, 2023, to December 31, 2023, encompassing both the west and east monsoon seasons. Sound propagation velocity calculations are based on the empirical Medwin equation, with a focus on a source depth of 10 meters at frequencies of 100 and 1,000 Hz in the North Natuna Sea. Simulation results indicate that both the west and east monsoon seasons exhibit similar and dense underwater acoustic wave propagation patterns. At a frequency of 100 Hz, the Transmission Loss ranges between 30 to 60 dB, with Shadow Zone areas extending from 0 - 500 meters and from 500 - 1,500 meters. Meanwhile, at a frequency of 1,000 Hz, the Transmission Loss ranges between 30 to 70 dB, with almost no Shadow Zone area present.